Review on the effect of correlated color temperature and spectrum power dstribution upon visual function / Nik Nursyazwani Nik Mustapha - Nik Mustapha, Nik Nursyazwani (Faculty of Health Sciences, 2015)
Purpose: This study was undertaken to review the effect of correlated color temperature (CCT) and spectrum power distribution (SPD) to the visual function. Review Design: About 50 established journals were reviewed in this study. There were four category of visual function assess in this study. The first one was ocular changed which involved pupil response. The second category was visual performance that consists of visual acuity, visual field, and color vision. The next category was visual experience which involving visual comfort, alertness, preferences, and brightness. The last category called as task performance including computer and paper based task as well as typing performance. Results: Higher pupil constriction in higher CCT which lead to the better visual acuity. Visual field was affected by both illumination and spectrum power distribution. Most of the finding is positive towards cool light CCT and short wavelength (blue) for spectrum power distribution. Conclusion: Different CCT and SPD of light will differentially affecting visual function.